Bringing inside-out online: coming together in a virtual environment. Issue 2 (17th February 2022) - Collica-Cox, Kimberly
Abstract: Inside-Out courses bring together traditional campus-based students and incarcerated students to learn alongside one another in a correctional setting. This novel approach to the delivery of educational programming has recognized benefits for both inside and outside students. This past year, the COVID pandemic prevented non-essential staff, such as college instructors, from physically entering correctional institutions. While most colleges and universities continued to provide educational services to its campus-based students virtually, they were prohibited from doing the same with their incarcerated students. The majority of correctional institutions have been resistant to using this technology because of security concerns, even though with proper planning, such programming can be provided successfully and safely. Although most Inside-Out programs were canceled during the Coronavirus pandemic, this article profiles one program that was able to continue virtually through the use of internet-based services at the Westchester County Department of Correction. Data from this feasibility study suggest that a virtual pedagogical approach has the ability to create positive learning experiences for inside and outside students. Results imply that increased programmatic opportunities could be available to more correctional institutions, even post-COVID, if correctional staff are open to the implementation of internet-based technology and willing to work collaboratively with outside program providers.